An economic prognostic study to examine the productivity of agricultural SMEs of Central Europe during the COVID-19 crisis - Imran, Ali; Sufyan, Ali; Tajammul, Ayesha; Gavurová, Beáta; Novák, Petr (Business: Theory and Practice, 2023)
In 2020, the COVID-19 pandemic disturbed the world's Agri-businesses. Several economies are attempting to demonstrate attempts to maintain agribusiness, the agriculture industry, and marketplaces, but distribution networks, access to markets, and affordable farm goods are still vulnerable. The poor and various disempowered populations, particularly those with lower buying power, have been harmed by the COVID-19 outbreak. This study examines the productivity of Central Europe's agricultural SMEs during the COVID-19 pandemic. A predictive model between independent and dependent factors was used to determine and forecast the index or risk for future agricultural SMEs' functioning. The Central European agricultural SMEs' performance indicators were used, such as agricultural output, production of agriculture goods and services, vegetable and horticultural products, fixed capital consumption, agriculture determinants' actual income index, absolute net agriculture business income index, and net agricultural entrepreneurial income. Our results reveal pre and post-COVID-19 agribusiness analyses and their implications for food distribution and sustainability. Our findings also revealed a widespread influence of COVID-19 on Central European areas. The study findings can help agricultural enterprises and policymakers manage the COVID-19 outbreak by providing essential recommendations and consequences.